Genome-wide identification of R-SNARE gene family in upland cotton and function analysis of GhVAMP72l response to drought stress - Li, Bingxuan; Zhou, Gen; Li, Yanbin; Chen, Xueting; Yang, Huiting; Li, Yan; Zhu, Minhua; Li, Libei (Frontiers in Plant Science, 2023)
Soluble N-ethylmaleimide-sensitive factor attachment protein receptors (R-SNAREs) mainly promoted the assembly of the SNARE complex to drive the final membrane fusion step of membrane transport. Previous research on R-SNAREs has mainly focused on development and growth and has rarely been involved in abiotic stress, especially in cotton. Here, we performed a comprehensive analysis of R-SNARE genes in upland cotton. In total, 51 Gh-R-SNARE genes across six phylogenetic groups were unevenly distributed on 21 chromosomes. Cis elements related to plant growth and response to abiotic stress responses were found in the promoter region of Gh-R-SNAREs. Nine Gh-R-SNARE genes were obviously upregulated under drought stress conditions by RNA-seq and qRT–PCR analysis. Among them, GhVAMP72l might be the key candidate gene contributing to drought stress tolerance in cotton by virus-induced gene silencing (VIGS) assay. These results provide valuable insights for the functional analysis of cotton R-SNAREs in response to drought stress and highlight potential beneficial genes for genetic improvement and breeding in cotton.